The Bioluminescence Phenomenon of Lomek Fishes (Harpadon nehereus) with their Luminous Bacteria - Kartika Dewi; Delianis Pringgenies; Haeruddin Haeruddin; Sakti Imam Muchlissin (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2018)
Lomek fish (Harpadon nehereus) is one of the most popular fish in Riau, which is widely distributed along the sea of Tanjung Balai Karimun, Riau Archipelago, Indonesia. Based on direct observation, this fish emits light when uncovered in open air and caused a phenomenon which called as bioluminescence. The purposes of this research were to reveale the cause of luminosity of the fish and to investigate the luminosity activity. This research was conducted in several stages ie; sampling and sample preparation, observation of bioluminescence activity, and isolation of luminous bacteria. The results showed that the bioluminescent of lomek fish occurred around the surface of the body. After 10 to 11 hours, the luminosity can be observed up to the innermost parts of the body. It is revealed that the bioluminescent of this fish is simply due to the presence of luminous bacteria on surface of its body. The bacteria could emit light on primary isolation after 48 h incubation and the light last for 8 h ahead.